Angiographic analysis of the lateral intercostal artery perforator of the posterior intercostal artery: anatomic variation and clinical significance - Eui-Yong Jeon; Young Kwon Cho; Dae Young Yoon; Young Lan Seo; Kyoung Ja Lim; Eun Joo Yun (Diagnostic and Interventional Radiology, 2015)

(untitled)
PURPOSEKnowledge of the anatomic variations of the posterior intercostal artery (PICA) and its major branches is important during transthoracic procedures and surgery. We aimed to identify the anatomic features and variations of the lateral intercostal artery perforator (LICAP) of the PICA with selective PICA arteriography.METHODSWe retrospectively evaluated 353 PICAs in 75 patients with selective PICA arteriography for the following characteristics: incidence, length (as number of traversed intercostal spaces), distribution at the hemithorax (medial half vs. lateral half), and size as compared to the collateral intercostal artery of the PICA.RESULTSThe incidence of LICAPs was 35.9% (127/353). LICAPs were most commonly observed in the right 8th–11th intercostal spaces (33%, 42/127) and in the medial half of the hemithorax (85%, 108/127). Most LICAPs were as long as two (35.4%, 45/127) or three intercostal spaces (60.6%, 77/127). Compared to the collateral intercostal artery, 42.5% of LICAPs were larger (54/127), with most of these observed in the right 4th–7th intercostal spaces (48.8%, 22/54).CONCLUSIONWe propose the clinical significance of the LICAP as a potential risk factor for iatrogenic injury during posterior transthoracic intervention and thoracic surgery. For example, skin incisions must be as superﬁcial as possible and directed vertically at the right 4th–7th intercostal spaces and the medial half of the thorax. Awareness of the anatomical variations of the LICAPs of the PICA will allow surgeons and interventional radiologists to avoid iatrogenic arterial injuries during posterior transthoracic procedures and surgery.